Cascading effects of N input on tritrophic (plant–aphid–parasitoid) interactions. Issue 21 (11th October 2016) - Chesnais, Quentin; Couty, Aude; Catterou, Manuella; Ameline, Arnaud
Abstract : We investigated how different levels of N input (no input, optimum, and excessive inputs) would impact host‐plant quality and subsequently alter tritrophic interactions, thus modulating bottom‐up forces. We showed that host N content, host suitability, and dietary specialization were major factors explaining the functioning of our studied system. Abstract: Because N is frequently the most limiting mineral macronutrient for plants in terrestrial ecosystems, modulating N input may have ecological consequences through trophic levels. Thus, in agro‐ecosystems, the success of natural enemies may depend not only from their herbivorous hosts but also from the host plant whose qualities may be modulated by N input. We manipulated foliar N concentrations by providing to Camelina sativa plants three different nitrogen rates (control, optimal, and excessive). We examined how the altered host‐plant nutritional quality influenced the performances of two aphid species, the generalist green peach aphid, Myzus persicae, and the specialist cabbage aphid, Brevicoryne brassicae, and their common parasitoid Diaeretiella rapae . Both N inputs led to increased N concentrations in the plants but induced contrasted concentrations within aphid bodies depending on the species. Compared to the control, plant biomass increased when receiving the optimal N treatment but decreased under the excessive treatment. Performances of M. persicae improved under the optimal treatment compared to the control and excessive treatments whereas B. brassicae parameters declined following the excessive N treatment. In no‐choice trials, emergence rates of D. rapae developing in M. persicae were higher on both optimum and excessive N treatments, whereas they remained stable whatever the treatment when developing in B. brassicae . Size of emerging D. rapae females was positively affected by the treatment only when it developed in M. persicae on the excessive N treatment. This work showed that contrary to an optimal N treatment, when N was delivered in excess, plant suitability was reduced and consequently affected negatively aphid parameters. Surprisingly, these negative effects resulted in no or positive consequences on parasitoid parameters, suggesting a buffered effect at the third trophic level. Host N content, host suitability, and dietary specialization appear to be major factors explaining the functioning of our studied system.